Th1 but not Th17 cells predominate in the joints of patients with rheumatoid arthritis. Issue 9 (6th December 2007) - Yamada, H; Nakashima, Y; Okazaki, K; Mawatari, T; Fukushi, J-I; Kaibara, N; Hori, A; Iwamoto, Y; Yoshikai, Y
Abstract : Objectives: Recent animal studies have revealed critical roles of interleukin (IL)17, which is produced by a newly identified subset of helper T cells, Th17 cells, in the development of autoimmune diseases including arthritis. However, in human rheumatoid arthritis (RA), detailed characteristics and the prevalence of Th17 cells are unclear. Methods: Peripheral blood mononuclear cells (PBMC) were obtained from 123 patients with RA and 28 healthy controls. Mononuclear cells were also prepared from synovial membrane or synovial fluid of 12 patients with RA. IL17 (IL17A) positive T cells were identified by a flow cytometer after ex vivo stimulation with phorbol myristate acetate and ionomycin. Disease activity was assessed with the 28-joint Disease Activity Score (DAS28). Results: IL17 positive cells were detected in CD45RO+ CD4 T cells. Most IL17 positive T cells produced neither interferon (IFN)γ nor IL4, but tumour necrosis factor (TNF)α similar to murine Th17 cells. The frequency of Th17 cells was neither increased in RA nor correlated with DAS28. Unexpectedly, the frequency of Th17 cells was significantly decreased in the joints compared with PBMC of the same patients with RA, whereas Th1 cells were more abundant in the joints than in PBMC. Conclusions: We could not obtain evidence that positively supports predominance of Th17 cells in RA. Further careful investigation is necessary before clinical application of IL17-targeting therapy.